Management of Intrahepatic Cholestasis of Pregnancy: Recommendations of the Working Group on Obstetrics and Prenatal Medicine - Section on Maternal Disorders - Hagenbeck, Carsten; Hamza, Amr; Kehl, Sven; Maul, Holger; Lammert, Frank; Keitel, Verena; Hutten, Matthias C.; Pecks, Ulrich (Geburtshilfe und Frauenheilkunde, 2021)
Intrahepatic cholestasis of pregnancy (ICP) is the most common liver disease specific to pregnancy. The cardinal symptom of pruritus and a concomitant elevated level of bile acids in the serum and/or alanine aminotransferase (ALT) are suggestive for the diagnosis. Overall, the maternal prognosis is good. The fetal outcome depends on the bile acid level. ICP is associated with increased risks for adverse perinatal outcomes, including preterm delivery, meconium-stained amniotic fluid, and stillbirth. Acute fetal asphyxia and not chronic uteroplacental dysfunction leads to stillbirth. Therefore, predictive fetal monitoring is not possible. While medication with ursodeoxycholic acid (UDCA) improves pruritus, it has not been shown to affect fetal outcome. The indication for induction of labour depends on bile acid levels and gestational age. There is a high risk of recurrence in subsequent pregnancies.
CRIS-Team Scopus Importer:2021-08-20
Keywords: bile acids; induction of labour; liver disease; pruritus; stillbirth; ursodeoxycholic acid